KEANEKARAGAMAN JENIS VEGETASI POHON DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) SAMBOJA KABUPATEN KUTAI KARTANEGARA KALIMANTAN TIMUR - Alhani, Fitra; Manurung, Togar Fernando; Darwati, Herlina (Universitas Tanjungpura, 2015)
The diversity of tree vegetation in Forest Areas With Special Purpose Samboja need to be described as supporting data in forest management and development activities as well as to support the research and education activities in the region. This study aims to determine species diversity of trees and vegetation beneficial provide basic scientific information about the diversity of vegetation types of trees, so it can be used as a data base in the management and utilization by the community and local government. Using a method of combination of lines and line terraced, on 9 (nine) lines with track width of 20m, 300m long track. Purposively placed transect cut contour assuming representation of forest conditions which was researched and diversity of vegetation types. Results of the study consisted of 342 tree species from 57 families. There are 44 types included in the IUCN (International Union for Conservation of Nature Red List of Threatened Species), CITES (Convention on International Trade in Endangered Species) 2 and 3 species included endemic. The highest importance value index for seedlings is Fordia splendidissima (Blume ex Miq.) Buijsen 25.2327876%, Sapling is Fordia splendidissima (Blume ex Miq.) Buijsen 32.0401352%, Poles is Macaranga gigantea (reichb.f. & Zoll.) Mull Arg. 29.8578411% and tree is Macaranga gigantea (reichb.f. & Zoll.) Mull Arg. 20.7934681%. Value Dominance Index (C) less than ( 5.0. Key Word: Diversity, trees, khdtk samboja, index value abudance, index value richnees